Decision-making under epistemic, strategic and institutional uncertainty during COVID-19: findings from a six-country empirical study - Asthana, Sumegha; Mukherjee, Sanjana; Phelan, Alexandra L.; Gobir, Ibrahim B.; Woo, J. J.; Wenham, Clare; Husain, Mohammad Mushtuq; Shirin, Tahmina; Govender, Nevashan; Nsour, Mohannad Al; Ukponu, Winifred; Ihueze, Adachioma Chinonso; et al. (BMJ global health, 2025)
Background Uncertainty is defined as limited knowledge or lack of predictability about past, present or future events. The COVID-19 pandemic management was significantly impacted by uncertainty, as the gaps between existing information and the necessary knowledge hindered decision-making. Current uncertainty literature primarily focuses on natural disasters, leaving a gap in understanding decision-making under uncertainty in times of public health emergencies. Analysing strategies for making decisions under uncertainty during the pandemic is crucial for future pandemic preparedness.Methods Using a comparative research design, we study the strategies governments used to make decisions under uncertainty during the COVID-19 pandemic. We collected data through desk reviews, stakeholder interviews and focus group discussions with stakeholders from government, academia and civil society from six purposefully selected countries: Nigeria, Singapore, South Africa, Bangladesh, Jordan and the UK.Results Regardless of political, geographic and economic context, all six countries adopted common strategies to make decisions under three types of uncertainties. Decision-making under epistemic uncertainty involved seeking expert advice and collecting evidence from other countries and international organisations. Decision-making under strategic uncertainty involved coordination, collaboration and communication. Decision-making under institutional uncertainty involved using or adapting pre-existing experiences, structures and relationships and establishing new institutions and processes.Conclusions We contribute to the theory and practice of public health crisis decision-making by presenting a unified national-level applied decision-making framework for events involving uncertainty. We provide practical guidance for approaches to enhance decision-making in future health crises that could also be used for other emergencies.